A Novel and Reliable Rat Model of Autism - Qi, Zhaoyao; Lyu, Mengke; Yang, Liping; Yuan, Haiyan; Cao, Yun; Zhai, Linlin; Dang, Weili; Liu, Juan; Yang, Fan; Li, Ying (Frontiers in Psychiatry, 2021)
Abstract Background: Autism spectrum disorders (ASD) is a complex neurodevelopmental disorder that lacks an ideal animal model to recapitulate the disease state of ASD. Previous studies have reported that transplanting gut microbiota of ASD patients into pregnant mice is sufficient to promote the changes of autism-like behavior in offspring. This study aims to explore whether fecal microbiota transplantation (FMT) can be used as a new method to establish the ASD animal model. Methods: We transplanted the fecal sample extract of ASD children into pregnant rats (rFMT) repeatedly to establish an ASD rat model (oFMT) and compare it with the classical valproic acid (VPA) model (oVPA). Results: First, we reveal that oFMT shows hypoevolutism and typical behavioral characteristics of ASD, consistent with the previous study. Second, the gut microbiota of oFMT mainly consists of Firmicutes and Bacteroidetes, recapitulating the abnormal gut microbiota of ASD. In oFMT, the abundance of Lactobacillus and Collinsella increased (Lactobacillus: oFMT 60.16%, oVPA 64.13%, oCON 40.11%; Collinsella: oFMT 3.73%, oVPA 1.39%, oCON 1.28%), compared with oVPA, gut microbiota also showed high consistency. Third, the expression of 5-hydroxytryptamine (5-HT) in oFMT serum increased, γ-aminobutyric acid (GABA) and norepinephrine (NE) in oFMT serum decreased. Fourth, the gut microbiota of oFMT also has some ASD characteristic gut microbiota not found in oVPA. Fifth, pregnant rat with VPA showed significant immune activation, while those with FMT showed relatively minor immune activation. Limitations: Although the mechanism of establishing FMT autism rat model (oFMT) has not clearly defined, the data show that the model has high structural validity, and FMT model is likely to be a new and reliable potential animal model of ASD, and will have potential value in studying gut microbiota of ASD. Conclusions: The FMT autism rat model has high structural validity, and the FMT model is likely to be a new and reliable potential animal model of ASD.